Microbial Metagenomics: A 360° approach - Vasquez Christodoulou, Marlen (My University, 2026)
▪ Experimental design ▪ Laboratory work for metagenomic studies: DNA extraction, metagenomic library preparation ▪ Metagenomics workflow, data analysis and sample characterization Dr. Giuseppe D’Auria, Dr. Jaqueline Dreyer- Lamm, Dr. José Eduardo González-Pastor